ESTABLISHING A BASELINE OF LOCAL & REGIONAL PRODUCE SOURCING EFFORTS AMONG NATIONAL NUTRITION INCENTIVE PRACTITIONERS - Souza, Kolia (My University, 2022)
Obesity in the United States has risen consistently since the 1970s, surpassing a 40 percent national obesity rate and increasing risk for excess morbidity and mortality, depression, pregnancy complications, and a range of chronic diet-related disease. Poor dietary intake is a major contributor to obesity and chronic health conditions. While fruit and vegetable intake significantly reduce the risk for obesity and other chronic health conditions, approximately 90 percent of U.S. adults do not consume the daily recommended servings of fruits and vegetables. This research study sought to establish a baseline for local and regional sourcing of fruits and vegetables in grocery retail through the Gus Schumacher Nutrition Incentive Program, or GusNIP, a federal subsidy providing Supplemental Nutrition Assistance Program (SNAP) participants incentives at the point of purchase. A series of semi-structured interviews were conducted among nutrition incentive grantees and practitioners through the Nutrition Incentive Hub, the technical assistance arm of the Nutrition Incentive Program National Training, Technical Assistance, Evaluation and Information Center (NTAE). Interviewees were selected from the 2019-20 Nutrition Incentive Hub annual technical assistance survey, and nine topics were included in thematic content analysis of fruit and vegetable supply chain development in the context of GusNIP: [1] definition of local, [2] motivations for sourcing locally, [3] steps taken to establish the local and regional sourcing program, [4] how the local and regional sourcing program is currently administered, [5] metrics used for the local and regional sourcing program, [6] supports for local and regional sourcing, [7] barriers to local and regional sourcing, [8] current local and regional sourcing needs, and [9] future plans/next steps. Three overarching themes emerged – relationships and partnerships, local foods economic development, and program capacity building and scalability. Although practitioner gaps in supply chain knowledge and macro-level barriers to local food sourcing inhibit program viability, context-specific supports help mitigate these challenges, in particular strategic partnerships for local and regional food system development. Future research should seek to better understand the interdependent relationship between these drivers and inhibitors in order to provide tailored technical assistance and capacity building to nutrition incentive grantees and practitioners.
Keywords: nutrition incentives; SNAP; healthy food access; food supply chain; food system